Intraorbital Wooden Foreign Body: A Case Report - Sitaula, Sanjeeta; Gautam, Vijay (Journal of Kathmandu Medical College, 2015)
Intraorbital foreign bodies are one of the commonly encountered orbital problems. They may be sight threatening due to the severity of injury or its complications and even life threatening if not managed appropriately. We present a case of a 24-year old female with history of fall injury from a tree with an impacted intraorbital wooden foreign body. The patient was treated with prophylactic intravenous antibiotics and prompt removal of the foreign body was done under general anesthesia in the operation theatre. The post operative visual recovery was excellent with significant improvement of ocular motility and limited improvement of ptosis. Hence even organic foreign bodies can have good prognosis with timely intervention. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12248 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014, Page: 119-121